Agile organization approach for competitiveness: perspectives from employees - Sim, Andrew Hui Ming (2022)
In today’s ever changing business landscape, being agile and agile methods have gained popularity with many organizations taking the plunge and transforming themselves to be agile while there are also a growing number of organizations which started as agile organizations from inception. Whether an organization has been successful in implementing agile or, if agile terminology is being used as a means to speed up projects, spreading team members thinly across multiple projects with aggressive timelines is worth investigating.